Actinomyces and Kartagener syndrome: Case report and literature review - Martinez Montalvo, Carlos Mauricio (2022)
Kartagener syndrome, which is part of the subgroup of the primary ciliary dyskinesias, predisposes to recurrent respiratory tract infections due to Haemophilus influenzae, Staphylococcus aureus and Streptococcus pneumoniae. The case of a patient with a diagnosis of Kartagener syndrome in whom colonization by Pseudomonas fluorescens and pneumonia complicated with empyema by Actinomyces spp is a rare association in the literature, which is described below.